Kajian Faktor Sumber Daya Manusia dalam Keterlambatan Proyek Jalan di Kabupaten Solok Selatan - Wulandari, Telsa; Wardi, Wardi; Anif, Bahrul (Universitas Batanghari, 2025)
A construction project can be said to be successful if it is completed on time, on budget and meets the specified quality. Many factors influence the success of a project, one of which is resource management. In the road construction project in South Solok Regency, the percentage of delays in completing the road project is relatively high in the medium-scale category. The purpose of the study was to identify human resource factors and dominant factors that cause delays in the implementation of road construction projects in South Solok Regency. This study will be conducted on a medium-scale road project from 2022 - 2023 on contractors who experienced delays in the implementation of road project work in South Solok Regency. In this study, purposive sampling techniques were used and questionnaires were distributed to respondents, then KMO and Bartlett tests, validity tests, reliability tests, MSA tests and rankings were carried out. The results of the analysis showed that the Project Manager, Site Manager, Site Engineer, and Executor factors were identified factors and this was proven by the analysis stages that had been carried out. The dominant factor causing delays in road construction projects in South Solok Regency based on the results of the ranking analysis, namely the Project Manager factor with an average value of 1.38519 with a standard deviation of 0.48093.